Online Reservation Website for Brayan Sehat Clinic Using Waterfall - Rosyid Mukti Wibowo; Afif Ramadhani; Adhitya Sofwan Al Rasyid; Kholil Abdi Prasetiyo; Gunawan Wibisono (Journal of Software Engineering and Multimedia (JASMED), 2025)
Brayan Sehat Clinic still uses a conventional reservation system that causes various obstacles, such as long queues, uncertain doctor schedules, patient data recording errors, and limited access to information. According to doctors at the clinic, the manual system often causes uneven schedule distribution and unbalanced staff workload. This research aims to design and build an online reservation system based on a website to improve service efficiency and patient comfort. System development uses the Waterfall method which consists of requirements analysis, system design with Use Case Diagrams and Entity Relationship Diagrams, implementation, testing, and maintenance phases. The system is built using PHP programming language and MySQL as a database with architecture consisting of front-end, back-end, and database that are integrated with each other. Testing was conducted using black box testing approach on seven main modules to ensure functionality runs according to user needs. Test results show that the system is able to overcome reservation problems by providing login/registration features, real-time doctor and schedule information, online consultation reservations, dynamic schedule management, and secure user data management. This website is expected to support the clinic's digital transformation by providing 24-hour reservation access and potential development of telemedicine features to improve healthcare service quality.